Transforming Learning and IT Management through Gamification - Prakash, Edmond C. (International Series on Computer Entertainment and Media Technology,, 2015)
This book explains how gamification, specifically enterprise gamification, can help mangers in multiple areas within an enterprise to improve attrition. Employee Engagement is an important component to foster employee relations with the organization. Gamification by its inherent design helps to increase engagement within an enterprise. Several successful case studies in Gamification are presented, which present new practical tips for Gamification for IT Management. By introducing general IT management concepts related to the specific environment managers work in, the authors then detail the benefits of introducing gamification in this very environment to resolve business issues. IT Managers, as well as HR professionals, Group Heads and Delivery Leaders will find this be a useful resource to understand how Gamification can improve their everyday work. The book can also be used as a reference for engaging learners and employees to improve their productivity in organizations.